Absattar Haji Derbisali and the Importance of His Works for the Development of Islamic Studies in Kazakhstan - Zhanabergenova, Dinara; Kairbekov, Nurlan (Journal of Al-Tamaddun, 2024)
Religion is an essential element in the existence of society and the culture of the people. It embodies universal human values and principles for the realisation of public relations. From the beginning of Kazakhstan’s independence to the present day, the issue of the spread of different religions in Kazakhstan, including Islam, remains relevant. The research aims to study the activity and creativity of Absattar Haji Derbisali in the context of the development of Islamic studies in Kazakh society. General scientific methods, the method of analysis and synthesis, as well as special historical methods: ideographic, historical-genetic, problem-chronological and comparative-historical, were used. As a result, it was possible to describe the main stages in the biography of the scholar Absattar Haji Derbisali. The significance of his works and achievements in the field of Islamic studies and its dissemination in Kazakhstan were described. The study established that it was Absattar Haji Derbisali who was the founder of the Kazakh School of Arabic Studies. This indicates that the spread of Islam in the territory of Kazakhstan took place based on the approaches and methods of this scholar. It has been established that Islamology was little explored and did not develop in Kazakh society. Based on this it was proved that the role of Absattar Haji Derbisali in the development of Islamic studies was extremely high, which had a positive impact on the development of the independent state. It has been established that his approaches to the management and organization of society are a priority since they provide for the interests of various religious cells. The practical value of the study lies in the fact that its results can be used in the development of training programmes for Islamic studies or in the deepening of knowledge about the peculiarities of the development of Islam in the culture of Kazakhstan.